1996
DOI: 10.3109/02770909609055374
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs of Adults with Asthma: Toward an Understanding of the Difference Between Symptomatic and Preventive Use of Inhaler Treatment

Abstract: The aim of this study was to examine the potential differences between beliefs relating to symptomatic and preventive inhaler treatment and to analyze the relationship between these beliefs and the use of inhalers by adult patients with asthma in general practice. Unstructured interviews with a stratified sample of 8 patients, taking a combination of salbutamol and beclomethasone inhalers, were used to develop themes for a structured interview, where questions relating to 8 main areas of interest were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 21 publications
1
24
1
1
Order By: Relevance
“…Poor asthma control was associated with poor asthma knowledge, a negative attitude, and more fears about the side effects of inhaled corticosteroids. Our findings are supported by previous studies that found that patient behavior and use of asthma medication are linked in a complex manner to personal attitudes and understanding of asthma and its treatment (9)(10)(11)23,24). In addition, patient satisfaction with their doctor (10) and good doctor-patient communication (25) are major factors influencing patient use of inhaled corticosteroids.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Poor asthma control was associated with poor asthma knowledge, a negative attitude, and more fears about the side effects of inhaled corticosteroids. Our findings are supported by previous studies that found that patient behavior and use of asthma medication are linked in a complex manner to personal attitudes and understanding of asthma and its treatment (9)(10)(11)23,24). In addition, patient satisfaction with their doctor (10) and good doctor-patient communication (25) are major factors influencing patient use of inhaled corticosteroids.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, poor patient knowledge of asthma and self-management skills as well as individual beliefs, attitudes, and behavior may contribute to poor adherence with prescribed asthma medication, which in turn will result in poor asthma control (8)(9)(10)(11)(12). To better understand asthma control from the patient's perspective, we have examined the attitudes, knowledge, and behavior of the adult asthmatics in the AIRE survey.…”
Section: Introductionmentioning
confidence: 99%
“…Perceiving drawbacks of asthma medications may contribute to worse adherence, whereas having strong beliefs in the benefits of asthma medications may contribute to better adherence (2)(3)(4). Patients taking asthma medications must concurrently weigh the necessity for medications and their concerns about potential adverse effects, both of which may affect adherence (3).…”
Section: Introductionmentioning
confidence: 98%
“…Studies by SPECTOR et al [10], MAWHINNEY and coworkers [11,12], YEUNG et al [13], RAND and coworkers [14][15][16] and others, which used electronic monitoring of pMDI dispensing, suggest that average adherence to asthma and COPD regimens is ,50% of prescribed, and may dip much lower [16]. Studies in both asthma and COPD also suggest that, while patients tend to under-use controller or maintenance therapies, symptom-relieving drugs such as bronchodilators are often overused [17,18].…”
mentioning
confidence: 99%